Changes in bone marrow and peripheral blood lymphocyte subset findings with onset of hepatitis-associated aplastic anemia. Issue 8 (25th February 2022) - Kakiuchi, Toshihiko; Eguchi, Katsuhide; Koga, Daisuke; Eguchi, Hiroi; Nishi, Masanori; Sonoda, Motoshi; Ishimura, Masataka; Matsuo, Muneaki
Abstract: Rationale: Hepatitis-associated aplastic anemia (HAAA) is a rare illness that results in bone marrow failure following hepatitis development. The etiological agent remains unknown in most HAAA cases. However, clinical features of the disease and immunotherapy response indicate that immune-mediated factors play a central role in the pathogenesis of HAAA. Activation of cytotoxic T cells and increase in CD8 cells could exert cytotoxic effects on the myelopoietic cells in the bone marrow. Patient concerns: A 15-month-old boy was brought to our hospital with complaints of generalized petechiae and purpura observed a week prior to hospitalization. His liver was palpated 3 cm below the costal margin, platelet count was 0 × 10 4 /μL, and alanine aminotransferase level was 1346 IU/L. A blood test indicated cytomegalovirus infection, and 3 bone marrow examinations revealed progressive HAAA. As the disease progressed to the 3 rd, 6 th, and 9 th week after onset, CD4 + T cells were markedly decreased, CD8 + T cells were markedly increased, and the CD4/CD8 ratio was significantly decreased. The number of B cells and natural killer cells decreased with time, eventually reaching 0.0%. Diagnosis: HAAA. Interventions: Rabbit antithymocyte globulin and eltrombopag olamine (a thrombopoietin receptor agonist) were administered. Outcomes: The patient's platelet count returned to normal, and bone marrow transplantation was avoided. The peripheral blood lymphocytes (PBLs) improved as the patient's general condition recovered. Lessons: This case demonstrates that HAAA induced by cytomegalovirus infection features decreasing CD4 + and increasing CD8 + PBLs as the bone marrow hypoplasia progresses. The PBLs return to their normal levels with the recovery from the disease. Our case findings thus support the involvement of immunological abnormality in HAAA.